HUBUNGAN POLA PEMBERIAN ASI DAN MP-ASI DENGAN PERTUMBUHAN ANAK 6-24 BULAN DI DESA ADIL MAKMUR KECAMATAN BOSAR MALIGAS KABUPATEN SIMALUNGUN TAHUN 2016 - Eva Ratna Dewi; Erna Mutiara; Jumirah Jumirah (STIKes Mitra Husada Medan, 2018)
Feeding patterns among children aged 0-23 months starting from the action of early initiation of breastfeeding, colostrum, exclusive breastfeeding and complementary feeding from the age of 6 months. This study aimed to analyze the relationship between breastfeeding and complementary feeding with growth of children 6-24 months in the Adil Makmur village, subdistrict of Bosar Maligas Simalungun, 2016.This type of research was an observational with cross-sectional study design conducted from March 2016 until December 2016. Population and sample in this study were all mothers of children aged 6-24 months in the Adil Makmur village subdistrict of Bosar Maligas Simalungun in 2016 which amounted to 61 mothers. Existing data were analyzed using multiple logistic regression.The results showed that the pattern of breastfeeding affect the growth of children with value of Exp (B) = 5.4 ;95%CI = (1.453-19.707) and (p=0.012), it meant that the mother who practice the poor breastfeeding pattern 5,4 times the risk to have the not normal child growth compared to the mother who practice the good breastfeeding pattern.It is suggested to Subdistrict of Bosar Maligas Puskesmas to continue monitoring the pattern of breastfeeding to the community in Desa Adil Makmur so that the pattern of breastfeeding given exactly in accordance with provisions of breastfeeding is correct as the recommended breastfeeding frequency. The pattern of giving, the type and frequency of MP-ASI must be in accordance with the age stage of the baby so that the baby's need for nutrition and nutrients is fulfilled. It is expected that the community, especially mothers, should improve the pattern of breastfeeding and breastfeeding properly and correctly which will affect the normal growth of children.